Power analysis in designing an experiment: The effect of acoustic treatments on mung beans - Nurul Ain Hazirah Abdullah; Khatijahhusna Abd Rani; Aishah Mohd Noor; Mohd Hafiz Fazalul Rahiman (Jurnal Ilmiah Matematika, 2021)
Recently, acoustic treatments have become an attention in agricultural studies. Many researchers found that acoustic treatments can be a supplemental factor in enhancing plant growth. However, the researches on this field have been mostly restricted to find the significant effect of their studies. Although extensive researches have been carried out, few studies do not report the sample size used in their experiment. Hence, this study will emphasise on the application of power analysis in the phase of designing an experiment which focus on the experiment to find the effect of acoustic treatments on mung beans. This paper presents a step-by-step guide to find the minimum number of sample size needed to conduct the experiment and how retrospective power analysis is calculated specifically for the data analysis using multivariate analysis of variance (MANOVA). Based on this study, the minimum total sample size estimated to conduct this experiment is 120 to 216. Upon conducting the experiment, the retrospective power is 97.3% and the effect size is 0.096. The effect size obtained can be a reference parameter for future experiment.